Pomegranate peel powder and extract improved weight control, lipid metabolism and gut microbiota in hamsters fed with standard american diets - Xingzhu Wu; Wallace Yokoyama; Yuqing Tan; Glenn Bartley; Ling Chen; James Pan; Priscila Alves Buongiorno; Jose Berrios; Tara McHugh; Zhongli Pan (Food Hydrocolloids for Health)
Pomegranate peel waste is a byproduct of juice processing and 1.6 million tons are produced globally each year. Pomegranate peels have a high dietary fiber content and unique polyphenol profile suggesting it may have health benefits. This study aimed to investigate the hypocholesterolemic and anti-obesity effects of pomegranate peel powder (PPP) and water extract (PPE) in Golden Syrian hamsters fed with high-fat (39 % fat calorie, HF) diets. Hamsters were fed either the HF, or the HF diet supplemented with 2.5 % or 5 % PPE (LE and HE, respectively), or 5 % or 10 % PPP (low-peel (LP) and high-peel (HP), respectively. After 4 weeks of feeding, hamsters gained 16.10- 33.82 g of weight and the feeding efficacy ranged from 0.10 to 0.18. The HP group had the lowest weight gain and feed efficacy while others were not significantly different. The HP group had significantly lower liver-to-body weight ratio (3.10 ± 0.08 % vs 3.65 ± 0.09 %), fasting blood glucose (68.11 ± 5.27 vs 82.94 ± 6.49 mg/dL), and hepatic lipid content (6.31 ± 0.26 vs 7.49 ± 0.22 g/100 g liver) compared to the HF group. PPP ingestion significantly increased LDL but decreased triglycerides. PPP and PPE feeding resulted in microbiota phyla Firmicutes-to-Bacteroidetes ratio characteristic of leaner phenotypes. HMG-CoAR and LDLR expression were reduced, suggesting that decreased uptake of LDL was not sufficient to lower plasma LDL, even with reduced cholesterol synthesis.